KUALITAS HASIL TANGKAPAN IKAN LAYANG DELES (Decapterus macrosoma) PADA KMN. BUKIT SAFA - Larasati, Rakhma Fitria; Tanjov, Yulia Estmirar; Adnyana, I Putu Agus (Jurnal Perikanan Unram, 2025)
KMN. Bukit Safa is a fleet that uses pelagic purse seine fishing gear with one ship. One of its main catches is the shortfin scad (Decapterus macrosoma). To maintain the quality of the caught fish and prevent damage that could lower its market value, it is important to implement proper handling methods on board the ship. This research was conducted with the aim of describing the physical condition of the fish after being brought on board and determining the freshness quality of the fish after the handling process on the ship. The research was conducted from February 23 to April 5, 2024, on the KMN. Bukit Safa, which is based at the Kendari Oceanic Fishing Port. The data collection method in this study used observation, interviews, and documentation techniques. To assess the freshness of the fish, it refers to the organoleptic evaluation SNI 2729:2021 on fresh fish. The data were analyzed quantitatively with reference to SNI 2346:2015 on sensory testing guidelines for fishery products and then analyzed descriptively. The physical condition of the fish brought onto the ship during the study was intact, lightly damaged, and heavily damaged. Based on the data analysis for the quality assessment results of the flying fish, there were several fish that experienced a decline in quality but were still in a fresh condition. The freshness of the fish is influenced by the quantity of the catch, the handling techniques used on the ship, the amount of ice used during handling, and the duration of the freshness assessment after the fish handling process on the ship.